U-bent Plastic Optical Fiber for Lard Adulteration Sensor in Edible Oil - Puspita, Ika; Kurniawan, Fredy; Hatta, Agus Muhamad; Koentjoro, Sekartedjo (Halal Center ITS, 2021)
A plastic optical fiber with the structure of U-bent was utilized as a sensor to detect lard adulterants in olive oil. The macro bending was formed on the plastic optical fiber with a bending radius of 10 mm, 12.5 mm, and 15 mm. The output spectra and intensity were measured to detect the existence of lard substance in olive oil. The U-bent plastic optical fiber sensor with a bending radius of 12.5 mm has the optimum performance to detect the lard adulterant substance in olive oil. It has a sensitivity of 4.6 a.u/% with 855 nm LED source and 10.07 a.u/% with 940 nm LED source in intensity-based measurement and 0.50 nm/% in spectrum-based measurement. The proposed sensor is the potential to give rapid detection on lard adulterant in edible oil.